2009
DOI: 10.1007/s10265-009-0219-7
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory function for water transport by adventitious roots of Ipomoea pes-caprae

Abstract: To determine the role of adventitious roots in supplying water to Ipomoea pes-caprae (L.) Sweet (Convolvulaceae), we examined the effects of water deficit on water uptake and the growth patterns of leaves and shoots. After stopping the water supply from the primary root or adventitious roots, the water-uptake rate of the other root system increased steeply within 90-100 min to a level of 90% of the pretreatment water-uptake rate of the whole plant. Thus, the primary and adventitious roots can compensate for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Additionally, osmotic stress damage is reduced by the waxy leaf surface and succulency. The vines of I. pes-caprae easily sprout adventitious roots, and the depth of primary roots can reach 3 meters, to make sure the plant gets water with little problem [ 23 ]. The above features indicate that I. pes-caprae can easily absorb water and limit the stomata transpiration, and thus possess strong drought tolerance under high temperature and strong light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, osmotic stress damage is reduced by the waxy leaf surface and succulency. The vines of I. pes-caprae easily sprout adventitious roots, and the depth of primary roots can reach 3 meters, to make sure the plant gets water with little problem [ 23 ]. The above features indicate that I. pes-caprae can easily absorb water and limit the stomata transpiration, and thus possess strong drought tolerance under high temperature and strong light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have been conducted on growth characteristics, root biomechanical properties, and anti-wind erosion ability of I. pes-caprae, S. littoreus, and V. rotundifolia. Kamakura and Furukawa [17] showed that the root system of I. pes-caprae belongs to adventitious roots (M-type). Divyasree and Raju [18] reported that S. littoreus possesses adventitious roots, and propagates through vegetative stolon formation.…”
Section: Introductionmentioning
confidence: 99%
“…When the stems are broken by a storm or when the stolons closer to the sea are washed away, they regrow quickly by vegetative reproduction [ 10 ]. The vines of I. pes-caprae easily sprout adventitious roots, and the depth of primary roots can reach 3 m, to make sure the plant is able to access water [ 11 ]. As a measure of reducing or eliminating osmotic stress and the toxic ions from seawater, I. pes-caprae accumulates large amounts of saline ions in vivo and has evolved a series of salt-tolerant mechanisms as an adaptive response to high-salt environments [ 12 ].…”
Section: Botanymentioning
confidence: 99%